Thermodynamic Characteristics of CH4 Adsorption on Shale at Different Temperatures. (28th July 2022) - Xue, Pei; Liang, Quansheng; Hao, Shiyan; Yin, Jintao; Gao, Chao; Zhang, Lixia; Zhao, Qianping
Abstract : In order to clarify the effect of temperature on the isosteric heat of adsorption of CH4 onto shale, by using the isothermal adsorption data of shale in the temperature range of 300 473 K and the pressure range of 0.08 14 MPa, the isosteric heat of adsorption is calculated, respectively, in the temperature range of 300 308 K, 338 373 K, and 423 473 K. The results show that the influence of temperature on the isosteric heat of adsorption of CH4 onto shale is mainly reflected in three aspects: the variation range of the isosteric heat of adsorption, the absolute adsorption capacity at which the isosteric heat of adsorption reach the maximum, and the change rate of the isosteric heat of adsorption. Specifically, as the temperature range moves to a higher range, the variation range of the isosteric heat increases significantly, and the absolute adsorption capacity decreases. The curve shape of the change rate of the isosteric heat of adsorption in different temperature ranges remained the same (decreased first and then increased), but the change rate increased gradually as the temperature range moved to a higher temperature range.